KOMPETENSI KEPALA SEKOLAH DALAM UPAYA MEWUJUDKAN SEKOLAH UNGGUL DI SDN 3 KALIWUNGU - Hartono, (UNISAN JURNAL, 2024)
This research was conducted with the aim of describing, revealing and explaining three things, namely the competence of the principal as a leader in improving the quality of learning and the problems faced in realizing a superior school and the principal's efforts in realizing a superior school. The data collection method used is the method of observation (observation), interviews (interviews), and documentation. The method of data analysis is inductive with the steps of preparing data reduction, displaying data, and drawing conclusions. The results of this study indicate that the principal's competence in improving the quality of learning is already owned by the principal of SMP IT Az Zahra Islamic Boarding School. In terms of output, SDN 3 Kaliwungu can always graduate students with a percentage of one hundred percent every year. These problems include the following: Most of the inputs are students with low to medium achievement. Lack of teaching staff, both in quality and quantity. Too many subject matter that is not accompanied by the amount of time (hours) provided. Lack of facilities and infrastructure such as study classrooms, student furniture, laboratory rooms and other supporting equipment such as computers, as well as small donations from the government in order to increase the need for facilities and infrastructure